Fatigue crack growth mechanisms of cast Ti-48Al (at. %) alloy - Hamad, S. (2000)
Substantial cost reduction for cast TiAl automotive parts could be achieved by eliminating hot isostatic pressing (HIPing) procedure during the material processing. In this respect, a cast Ti-48Al (at %) intermetallic alloy is evaluated in the non-HIPed condition with the objective to establish the fatigue crack growth response and identify the fracture mechanisms. For this purpose, a series of fatigue crack growth tests were performed on the alloy with three different microstructures, with a load ratio, R=0.1, in both air and vacuum environment. Environment effect is manifested in the threshold ΔK levels of 9.6 and 13 MPa√m for crack growth response in air and vacuum, respectively. In the intermediate range of crack growth rates between 10 -5 to 10-3 mm/cycle, crack bridging by shear ligament formation describes the crack growth process, with ΔK varying from 13 to 35 MPa√m. Extensive crack bridging effect in the duplex microstructure is reflected in the crack growth retardation which reaches the lowest minimum crack growth rate at 2×10-6 mm/cycle in each of the three crack bridging stages observed. Other fatigue damage mechanisms observed are crack deflection, crack branching, stepped crack growth and microcracks initiation in the crack tip plastic zone, particularly at near threshold crack growth.